Adult time-mortality response and changes in reproductive attributes in Callosobruchus maculatus (Fab.) following UV irradiation - Islam, M Saiful; Mustari, Sharmin (Journal of Life and Earth Science, 2011)
Using 254nm UV radiations of exposure periods from 2 to 16 min against adults. Time mortality response of the cowpea weevil, Callosobruchus maculatus (Fab.) (Coleoptera: Bruchidae), adults and alterations in vital reproductive attributes as fecundity, immature duration, adult emergence and adult longevity of the beetles from parental through F1 generation have been estimated. Time mortality response of the adults of the cowpea weevil Callosobruchus maculatus (Fab.) (Coleoptera: Bruchidae), and alternations in vital reproductive attributes is fecundity, immature duration, adult emergence and longevity from parental through F1 generation using 254nm UV radiations of response periods from 2-16min have been estimated. Results show that an exposure time to kill 50% of the adults is around 20 min (LT50 = 19.99min), and irradiation significantly reduced egg-laying (P<0.001), lengthened immature durations (i.e. larval and pupal developmental periods; P<0.05), decreased adult emergences as well as longevity in both sexes (P<0.001) in the parental generation. The effects of the UV-rays on F1 progenies, however, were less pronounced than that expressed in the parental generation, but the immature duration was significantly increased (P<0.01) but the longevity in both sexes was significantly reduced (P<0.001). Relevance of this study in relation to prospective phytosanitary treatments of the stored pulses with UV-rays has been discussed. Key words: UV irradiation; Callosobruchus maculatus; time-mortality response; reproductive attributes; stored pulses DOI: 10.3329/jles.v5i0.7343 J. Life Earth Sci., Vol. 5: 17-22, 2010